Determinants of economic growth regencies/cities in Jambi Province with dynamic panel data approach - Hajri Puja Pratama; Syaparuddin Syaparuddin; Emilia Emilia (Program Magister Ilmu Ekonomi Pascasarjana Universitas Jambi, 2022)
This study aims to analyze the determinants of economic growth Regency/City in Jambi Province. The factors considered to be the determinants of economic growth are lagged economic growth, government expenditure, household consumption, labor, and infrastructure. This study used time series data from 2011-2020 and cross-section 11 regencies/cities in Jambi province. The analysis tool used in this study is dynamic panel data regression. The results of the dynamic panel data regression show the generalized system method of the moment model as the best model. Based on the analysis results, lagged economic growth had a significant positive effect. In the short term, labor had a significant negative effect, and infrastructure had a significant positive effect. In contrast, government expenditure and household consumption did not significantly affect economic growth. In the long run, infrastructure has a significant positive effect, while government expenditure, labor, and home consumption have no significant effect on economic growth.